PERBEDAAN EMOTIONAL HANDLING DITINJAU DARI HASIL INTERVENSI EMOTIONAL EXPERIENCE WRITING (EXPRIT) ANTARA REMAJA LAKI-LAKI DAN PEREMPUAN DI PANTI ASUHAN - Resi Raf Sanjani; Sri Nugroho Jati; Elly Trisnawati; Widya Lestari (Universitas Islam Indonesia, 2022)
The differences in emotional handling between male and female adolescents lead to differences in the way of thinking, feeling, and behaving. This experimental research used the Emotional Experience Writing (EXPRIT) model as an intervention for 15 orphans (8 male adolescents from the Tunas Melati Orphanage and 7 female adolescents from Tunas Harapan Orphanage in Pontianak City aged 12-18 years). There were rapport-building sessions at the start of the study as well as five intervention sessions. Qualitative data were collected by coding techniques on the subject's writing, and The Emotional Handling Scale was used to collect quantitative data. The data analysis is using paired t test. This study revealed differences in emotional handling abilities between the two groups of adolescents based on gender. The t test scores were higher than the t table in both orphanages. This result shows that the EXPRIT model as an intervention, affects the ability to deal with emotions for both genders in the form of different models of emotional control.